(1)取p=n,q=1,则an+1=an+a1=an+2
∴an+1-an=2(n∈N*)
∴{an}是公差为2,首项为2的等差数列
∴an=2n(4分)
(2)∵-+-++(-1)n-1=an(n≥1)①
∴-++(-1)n-2=an-1(n≥2)②
①-②得:(-1)n-1=2(n≥2)bn=(-1)n-1(2n+1+2)(n≥2)
当n=1时,a1=∴b1=6满足上式
∴bn=(-1)n-1(2n+1+2)(n∈N*)(9分)
(3)Cn=3n+(-1)n-1(2n+1+2)•λ
假设存在λ,使Cn+1>Cn(n∈N*)3n+1+(-1)n(2n+2+2)•λ>3n+(-1)n-1(2n+1+2)•λ[(-1)n(2n+2+2)-(-1)n-1(2n+1+2)]•λ>3n-3n+1=-2•3n(-1)n(3•2n+1+4)•λ>-2•3n
当n为正偶函数时,(3•2n+1+4)λ>-2•3n恒成立λ>(-)max=(-)max
当n=2时(-)max=-
∴λ>-
当n为正奇数时,-(3•2n+1+4)•λ>-2•3n恒成立
∴λ<()min=()min
当n=1时[]min=
∴λ<
综上,存在实数λ,且λ∈(-,)(16分)